Analisis Penerapan Metode First In First Out (FIFO) terhadap Efisiensi Manajemen Operasional pada Toko Kelontong Reni - Farhan Fitra Rafifan; Rahma Ulfa Maghfiroh (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
Inventory management is a crucial aspect in improving operational efficiency, particularly for micro, small, and medium enterprises (MSMEs) such as grocery stores. This study aims to analyze the effect of implementing the First In First Out (FIFO) method on operational efficiency at Reni Grocery Store. Prior to applying FIFO, the inventory system in the store was poorly organized, often resulting in losses due to expired or damaged goods. Since March 2025, FIFO has been implemented by placing older items at the front of the shelves, while new items are consistently placed at the back, accompanied by routine checks of expiration dates. This research employs a qualitative approach using in-depth interviews with the store owner as the main subject. The findings indicate that FIFO positively influences operational efficiency, as reflected by reduced expired goods, improved stock recording, and more organized product flow. These results are consistent with previous studies, such as Pratama & Sari (2020), which showed FIFO reduced losses by up to 25%, as well as Suharto et al. (2021) and Rahman (2022), who emphasized that FIFO enhances stock accuracy and distribution efficiency. Nevertheless, this study also reveals limitations, including limited storage space and a lack of manpower for routine checks, which prevent FIFO implementation from being fully optimal.